2012
DOI: 10.1007/s10930-011-9388-z
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Cell Surface-Associated Keratin 8 and Its Implications for Enhanced Plasmin Activity

Abstract: Serum PSA, Gleason score, pathological stage, and positive surgical margins are currently used as predictors for disease recurrence. However, these criteria are less than precise in predicting disease outcome, with only 10% specificity at the 90% sensitivity level. Keratins are intermediate filament proteins that are contained within normal epithelia. However, human prostate cancer tissue shows differential immunohistochemical staining of keratin 8 (K8) when compared to normal prostate tissue. Our immunofluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…However, the effect of RAS on cytokeratin 8 was not observed in all cell lines examined as 293T cells transfected with oncogenic HRAS failed to show an increased expression of cytokeratin 8, whereas S100A10 and annexin A2 expression were elevated in these cells (Supplementary Figure S3). Cytokeratin 8 expression has been reported on the surface of cancer cells and only in certain epithelial cells [48, 5456] and to be upregulated in HRAS expressing epidermal cells [57]. Nonetheless, the loss of cytokeratin 8 expression rather than its upregulation is associated with metastasis and chemoresistance [58].…”
Section: Resultsmentioning
confidence: 99%
“…However, the effect of RAS on cytokeratin 8 was not observed in all cell lines examined as 293T cells transfected with oncogenic HRAS failed to show an increased expression of cytokeratin 8, whereas S100A10 and annexin A2 expression were elevated in these cells (Supplementary Figure S3). Cytokeratin 8 expression has been reported on the surface of cancer cells and only in certain epithelial cells [48, 5456] and to be upregulated in HRAS expressing epidermal cells [57]. Nonetheless, the loss of cytokeratin 8 expression rather than its upregulation is associated with metastasis and chemoresistance [58].…”
Section: Resultsmentioning
confidence: 99%
“…Unlike other endocytotic receptors, such as mannose receptor or CLEC9A, DEC205 usually targets to late endosomes and lysosomes (14,43); thus, DEC205 may also bind keratins on cell debris in phagosomes or early endosomes and transport them to late endosomes and lysosomes for more efficient antigen presentation. It is noteworthy that keratins are not only expressed inside cells, they are also found on the surface of some cell types such as carcinoma cells (30,(48)(49)(50). Evidence shows that extracellular acidification is usually associated with inflammation and tumorigenesis and is treated as a danger signal by the immune system (51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…KRT8, which is sensitive to TNF-dependent epithelial apoptosis, 53 has been proved to be an important distinguishing marker in prostate cancer. 54 Furthermore, we observed that both lnc-SNURF-1 and KRT8 showed significantly increased expression in the re-annotated exon array (Fig. 7B) and other RNA-seq data (Fig.…”
Section: Systematic Evaluation Of Predicted Cancer-related Lncrnasmentioning
confidence: 64%